Correction: Ci et al. Enhanced Delivery of Imatinib into Vaginal Mucosa via a New Positively Charged Nanocrystal-Loaded in Situ Hydrogel Formulation for Treatment of Cervical Cancer. Pharmaceutics 2019, 11, 15 - Li-qian Ci; Zhi-gang Huang; Feng-mei Lv; Jun Wang; Ling-lin Feng; Feng Sun; Shui-juan Cao; Zhe-peng Liu; Yu Liu; Gang Wei; Wei-yue Lu (MDPI AG, 2023)
In the original publication [...]